A qualitative evaluation of a Young Parents Program (YPP) – Parent and facilitator perspectives. (1st February 2019) - Strange, Cecily; Bennett, Elaine; Tait, Maggie; Hauck, Yvonne
Abstract: Issue addressed: Young parents (<25 years) have lower engagement with health and community services and are more likely to experience negative outcomes in the perinatal period compared to older parents. The aim of this study was to evaluate the short to medium‐term outcomes of the Young Parents Program (YPP), specifically designed to engage and support young parents, using responsive and codesign strategies in a community setting. Methods: A qualitative case study used data from interviews with participating parents (n = 20) and a focus group with YPP facilitators (n = 5). Results: The findings report on the following short to medium‐term YPP outcomes for parents and children. Young parents: are engaged in early parenting services that are welcoming, nonjudgemental and holistic; build parenting skills, knowledge, confidence and are tuned into their infants' needs; are empowered to codesign program activities to meet their parenting and nonparenting needs; have developed friendships and a social support network in their local community; and, are linked into community services and resources. Their children are cared for and stimulated with age‐appropriate interactions and play. Conclusion: Flexible, responsive and codesigned programs for young parents are effective means of connecting parents to services, social support networks and can provide learning opportunities, which enhance both child and parent attachment and development. So what?: Qualitative evaluation provides an understanding of contextual factors – required to inform effective design and delivery of young parent community programs.